A New Road Safety and Street Light Intensity Control Technique (International Journal of Innovative Research in Computer Science & Technology, 2022)
Street lightings is particular critically concerned for the communal authoritie in a developing  country because of it strategics importances for the  economical & social stabilities. The paper's main goal is to  make roads safer by using an intelligent lighting system  that uses less energy. System feature automatically street  light brightness adjustment based on the vehicle  movements, as well as automatic street light switching ON  and OFF based on ambient light. Every given distance, a  street light module is put one after the other. The suggested  technology also seeks to reduce traffic accidents by  identifying whether or not the driver has consumed alcohol.  An alcohol sensor module with a skin sensor, breath  alcohol sensor, and proximity sensor can be used to do this.  The proximity sensor aids in detecting any type of  carelessness, while skin sensors & alcohol sensor identify  presences of the alcoholic content. Novelty of paper is  effectively reducing consumption of energy of the road light by the controlling of intensity of the streets lights,  detecting both the human & vehicular movements, and  preventing injury and death caused by drunk driving by  pre-sensing the alcohol content in drivers in a simple and  cost-effective manner. The suggested system may be  implemented on a wide scale by the government, and other  features can be added in the future, such as a GSM module  that can be used to send a notification to the traffic police  if the motorist tries to remove the alcohol detection module  in any way. In the future, an overspeed detection  technology might be combined with street light control.
Keywords: Alcohol; LDR; Vehicle; Sensor; Street Light